International business English self-study cassette sets 1-2 [soundrecording] - Jones, Leo; Alexander, Richard (Cambridge Cambridge University Press, 1989)
A self-study on the fundamentals of English compositions and communication skills in business.
Keywords: English language -- Business English; Communication; Language